FATTY ACIDS PROFILE OF MEAT, MUCOSAL sIgA CONCENTRATION AND PRODUCTION INDEX OF BROILER AS A RESPONSE TO CHLORELLA sp. ADMINISTRATION IN THE DIET - Sugiharto, S.; Henckel, P.; Lauridsen, C. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
This study was carried out to investigate the effect of different levels of Chlorella sp. in the form ofmeal administrated in the diet of broilers throughout their life upon FA profile of the breast muscle,mucosal secretory IgA (sIgA) concentration and production index (PI) of broiler. Allotted in 18 pens, thetotal of 90 Ross day old chicks were assigned in completely randomized design by 3 of dietarytreatments (T1: control (basal diet without enrichment of Chlorella sp.); T2: basal diet enriched with 5-gChlorella sp./kg feed; T3): basal diet enriched with 10-g Chlorella sp./kg feed. At d-36, skinless breastmeat was collected for FA determination. Practical standard of vaccination was performed to activateantibodies production and at d-36 gut mucosa was collected for sIgA analysis. Chlorella sp.administration had no significant effect (P>0.05) on the FA profile of breast muscle, mucosal sIgAconcentration and producton index of broiler. In conclusion, the level and ratio between n-3 to n-6polyunsaturated fatty acids (PUFA) as well as the nature of dietary PUFA source determine tissue PUFAcomposition. Beside through eicosanoid, Chlorella sp. may affect mucosal sIgA production throughcytokines mediated effect. Although Chlorella sp. administration does not improve the production indexof broiler, this treatment may produce broiler meat with lower fat content.